2021
DOI: 10.1021/acs.jpcb.0c10263
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Encountered Applying Equilibrium and Nonequilibrium Binding Free Energy Calculations

Abstract: Binding free energy calculations have become increasingly valuable to drive decision making in drug discovery projects. However, among other issues, inadequate sampling can reduce accuracy, limiting the value of the technique.In this paper we apply absolute binding free energy calculations to ligands binding to T4 lysozyme L99A and HSP90 using equilibrium and non-equilibrium approaches. We highlight sampling problems encountered in these systems, such as slow side chain rearrangements and slow changes of water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 78 publications
2
74
0
Order By: Relevance
“…It has been observed that relying on the statistical uncertainties from the ∆G estimators, either analytical expressions, or bootstrapped values, may not be reliable. 5,38 Therefore, in this work we rely on independent repeats of the whole free energy calculation procedure to gain access to the variation of the ∆G estimates. 14,46 Subsequently, we incorpo-rate both, uncertainties from the independent replicas and statistical uncertainty from the estimator by means of bootstrap into a single uncertainty value.…”
Section: Sources Of Statistical Uncertaintymentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that relying on the statistical uncertainties from the ∆G estimators, either analytical expressions, or bootstrapped values, may not be reliable. 5,38 Therefore, in this work we rely on independent repeats of the whole free energy calculation procedure to gain access to the variation of the ∆G estimates. 14,46 Subsequently, we incorpo-rate both, uncertainties from the independent replicas and statistical uncertainty from the estimator by means of bootstrap into a single uncertainty value.…”
Section: Sources Of Statistical Uncertaintymentioning
confidence: 99%
“…This allows one to explicitly include the different apo and holo end-states into the same calculation 17 . Several recent applications of the NEQ approach on model host-guest systems showed promising results for the calculation of absolute binding free energies 5,27,37 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that relying on the statistical uncertainties from the ∆G estimators, either analytical expressions, or bootstrapped values, may not be reliable. 4,35 Therefore, in this work we rely on independent repeats of the whole free energy calculation procedure to gain access to the variation of the ∆G estimates. 13,42 Subsequently, we incorporate both, uncertainties from the independent replicas and statistical uncertainty from the estimator by means of bootstrap into a single uncertainty value.…”
Section: Sources Of Statistical Uncertaintymentioning
confidence: 99%
“…This allows one to explicitly include the different apo and holo end-states into the same calculation 16 . Several recent applications of the NEQ approach on model host-guest systems showed promising results for the calculation of absolute binding free energies 4,25,34 .…”
Section: Introductionmentioning
confidence: 99%